Coupled Fixed Point Theorems under Weak Contractions - Y. J. Cho; Z. Kadelburg; R. Saadati; W. Shatanawi (Discrete Dynamics in Nature and Society)
Cho et al. [Comput. Math. Appl. 61(2011), 1254–1260] studied common fixed point theorems on cone metric spaces by using the concept of c-distance. In this paper, we prove some coupled fixed point theorems in ordered cone metric spaces by using the concept of c-distance in cone metric spaces.